Implementation of the School Literacy Movement during the Covid-19 Pandemic at Elementary Schools - Andi Mulawakkan Firdaus (IAIN Palopo, 2021)
Reading is the most suitable alternative to improve education children's literacy while literacy is the ability to create interpret a meaning through the text. This research aims to know the implementation of the School Literacy Movement (GLS), especially in increasing student interest in reading during the Covid-19 pandemic. This type of research was a quantitative or experimental research (pre-experimental design). As for the results Inferential statistical analysis was carried out using the t-test formula, it is known that tCount obtained 12.648 with a frequency of df = 25-1 = 24, at a significant level = 0.05 or 5% obtained t table 2.063. So the t-count was 12, 648 2,063 this shows that He is rejected and H is accepted. Based on the results of the study and referring to the hypothesis that the researcher set, it can be concluded that there is a significant effect of implementation of the School Literacy Movement (GLS), especially reading interest at the fifth grade students at Bakung 2 Sudiang Elementary School, Biringkanaya District, Makassar City.